Spectral Properties and Physical Extent of Pyroclastic Deposits on Mercury: Variability Within Selected Deposits and Implications for Explosive Volcanism. Issue 5 (13th May 2020) - Besse, S.; Doressoundiram, A.; Barraud, O.; Griton, L.; Cornet, T.; Muñoz, C.; Varatharajan, I.; Helbert, J.
Abstract: Explosive volcanism on the surface of planet Mercury is visible through the pyroclastic deposits that surround morphologic features often identified as the vent. Those deposits are known as faculae. The understanding of explosive volcanism provides important information on Mercury's geological, thermal, and volcanic history. Observations by the MESSENGER spacecraft are used to analyze in detail the spectral properties of 14 selected faculae with the aim of understanding their chemical and physical properties. Scientific observations obtained by the MASCS instrument are particularly suitable for this task, although their observational and geometrical constraints limit definitive conclusions. Nonetheless, spectral properties in the visible, ultraviolet and near‐infrared indicate that the selected faculae are probably larger than visible in images solely. Spectral parameters provide a means to isolate Mercury's pyroclastic deposits with respect to Mercury's average spectral behavior. The similar spectral behavior of the visible, ultraviolet and near‐infrared domains suggests that the amount of mixing of pyroclastic materials with the underlying material, the differences in grain sizes between and inside the faculae, and the presence of opaque/mineral phases, could play significant roles in the spectral properties observed. Observations by the BepiColombo mission in nadir configuration covering a large range of phase angles will be highly complementary to the MESSENGER observations. Plain Language Summary: The presence of volcanism on Mercury has been confirmed from observations taken by the NASA MESSENGER mission in 2011. As on Earth, various styles of volcanism have been detected; explosive volcanism which involves a low volume of lava and high volume of gas, and effusive volcanism, which is richer in lava and poorer in gas. Using observations in the near‐infrared and visible spectral domain, this analysis aims at better characterizing the physical and chemical properties of the deposits resulting from explosive volcanism. In this manuscript, it is shown that the scale of deposits resulting from explosive volcanism has been underestimated, which cascades to a potential underestimation of the quantity of gas present in the interior of Mercury through its history. Additionally, it is shown that the amount of mixing of pyroclastic materials with the underlying material, the differences in grain sizes between and inside the faculae, and the presence of opaque/mineral phases, could play significant roles in the spectral properties observed in near infrared and visible spectral domain. Unfortunately, the limitations in the measurements from MESSENGER complicate the exploration of physical and chemical properties. These issues will be better explored with the BepiColombo mission, the next mission to explore the surface of Mercury. Key Points: Variations in spectral properties are correlated with the distance from the source Grain size, regolith mixing, and/or the presence of an opaque/mineral are possible controlling factors in the spectral variability observed Faculae (e.g., Bitin, Agwo, Orm) have a larger spatial extent than image data alone suggest